2008
DOI: 10.1088/1748-6041/3/4/044114
|View full text |Cite
|
Sign up to set email alerts
|

Release behavior of cupric ions for TCu380A and TCu220C IUDs

Abstract: We immersed copper T380A and T220C IUDs in simulated uterine solution (SUS) and also in simulated body fluid (SBF). The release rate and corrosion products of copper ions after soaking in SUS and SBF for different time spans were studied by an atomic absorption spectrophotometer, scanning electron microscopy with energy dispersive x-ray microanalysis (SEM/EDX) and x-ray diffraction. The highest corrosion rate of the TCu380A IUD was obtained on the first day, while the highest corrosion rate of the TCu220C IUD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
14
0
3
Order By: Relevance
“…The initial rapid release of cupric ion from these Yuangong Cu-IUDs was less than that of TCu380A IUD [20] , which might lead to smaller side effects related to burst release. The copper surface area of Yuangong 365 Cu- IUD was 365 mm 2 , and the real copper surface area of TCu380A IUD was 400 mm 2 [20] .…”
Section: Discussionmentioning
confidence: 92%
“…The initial rapid release of cupric ion from these Yuangong Cu-IUDs was less than that of TCu380A IUD [20] , which might lead to smaller side effects related to burst release. The copper surface area of Yuangong 365 Cu- IUD was 365 mm 2 , and the real copper surface area of TCu380A IUD was 400 mm 2 [20] .…”
Section: Discussionmentioning
confidence: 92%
“…In our earlier study we reported the initial burst release of Cu in the first three days from two commercial TCuIUDs followed by a sustained release in simulated uterine and body fluids. Further, we also showed CuIUDs get corroded faster when implanted in rat uterus (in vivo) than in simulated fluids (in vitro) (Cao et al 2008). In this study, we analyzed the Cu ion concentration dependent cytotoxicity to L929 mouse fibroblasts cells and correlated with that due to the burst release extracts from two commonly used CuIUDs -TCu220C and TCu380A.…”
Section: Discussionmentioning
confidence: 95%
“…However, their total Cu surface areas were different: 265 and 400 mm 2 respectively. Furthermore, the surface of the fine Cu wire wound on TCu380A appeared to have micro-cracks, compared to a smoother surface on Cu tubes, on the tested TCuIUDs (Cao et al 2008).…”
Section: Cu Ion Extracts From the Iudsmentioning
confidence: 89%
See 2 more Smart Citations